(3GdQSGdI aj GdNhGUs - (3CMeO Hf EHQGgje Hf CHj NGdO GdeJWHH,J (B395 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI habc Gddg ddCNdGb GdLejdI , hgOGc Edi cd aVjdI, hCYGPc ef GdRjZ Yf GdgOi Gdejd Edi Gdghi EJUd Hj CSYOc Gddg eG JWdbg aj eLdSc ef jYjH cJGHj aj GdMjhGf hcJGHj aj GdSeGFe s
(3BNQgG (B:s
(3hjSO QCS GdHhJb , hjZTi aMekG, hjJQc djdI , Ke jNQL hpjNP CZHQ ONdI CHjV , jQaY GdMGLI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3fSNI bdjdI GdfbW hHgG JbWjYs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B137s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B105 s
Keywords: (3GdWHs